The Discursive Construction of National Identities - DE CILLIA, RUDOLF and REISIGL, MARTIN and WODAK, RUTH (Discourse & Society, 1999)
The concept of the nation as an imagined community has gained importance in the relevant literature during the last decade. How do we construct national identities in discourse? Which topics, which discursive strategies and which linguistic devices are employed to construct national sameness and uniqueness on the one hand, and differences to other national collectives on the other hand? These questions were investigated in our study on the Austrian nation and identity. Taking several current social scientific approaches as our point of departure, we have developed a method of description and analysis of these phenomena which has applications beyond the discursive production of national identity in the specific Austrian example studied. By focusing particularly on the discursive construction of (national) sameness, this study has broken new ground in discourse-historical analysis, which until now has mainly been concerned with the analysis of the discursive construction of difference.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTU3OTI2NTk5MDEwMDAyMDAy